Mengenal Model Kooperatif Numbered Head Together (NHT) Untuk Pembelajaran Anak Usia Dini - Palupi, Diana Indah; Rahmani, Emma; Yusnita, Erlin; Pertiwi, Hikmah; Gustina, Hera; Priyanti, Nita (LP. Ma'arif Janggan Magetan, 2023)
There are many learning models that can be practiced at all levels of education, one of which is the Numbered Head Together (NHT) cooperative learning model. This article discusses the NHT learning model which explains the history, definition, disadvantages and advantages, main characteristics, principles, and objectives of this NHT model. This article was created considering that the NHT learning model is still rarely used by educators, especially in learning at the unit level of early childhood education. So it is hoped that this article can expand knowledge, especially among educators as parties who have an important role in providing education for early childhood. This research uses a qualitative type of research by referring to descriptive analysis from various relevant sources as well as studies from research results that have applied the NHT learning model to early childhood learning. The type of study used is a literature study by collecting information from books, journals, article discussions, and others. The results of this study are known that the NHT learning model can improve children's cognitive and social abilities and can influence student interaction patterns and has the aim of improving academic mastery.